IMPLEMENTASI PROGRAM ASISTENSI MENGAJAR DALAM PENINGKATAN KUALITAS PEMBELAJARAN DI SD NEGERI 060888 MEDAN SUNGGAL: Penelitian Tindakan Kelas - Reflina Sinaga, Eka Margareta Sinaga, Geofani Situmorang, Wihi Efesus; Rica Lisdawati, Esra Sesi Marsina, Siswita Anggreni Ginting, Lasroima Naomi Silaban (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
The teaching assistance program is an effort to enhance the quality of elementary education and foster the professional character of prospective teachers. The issue addressed in this study is the need to optimize student involvement in the elementary school learning process, as part of the Merdeka Belajar Kampus Merdeka (MBKM) policy. This study aims to describe the implementation and impact of the teaching assistance program on improving learning quality at SDN 060888 Medan Sunggal. The method used was a combination of observational and instructional approaches, in which student teachers served both as classroom observers and instructors. The results indicate that students actively participated in academic, non-academic, and administrative school activities. The program significantly contributed to the development of soft skills such as communication, collaboration, and classroom management, as well as hard skills including the use of digital learning media and lesson planning. It is concluded that the teaching assistance program not only improves students' teaching competencies but also contributes positively to more effective and meaningful learning processes in elementary schools